1999
DOI: 10.1016/s1010-7940(99)00025-1
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial protection in operations requiring more than 2 h of aortic cross-clamping

Abstract: Long, complex operations requiring more than 2 h of cross-clamping can be performed safely with our method of cardioprotection based on continuous retrograde infusion of tepid, hyperkalemic, undiluted blood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…Atrial fibrillation is observed in 7 to 40% of the cases after coronary bypass surgery [30,31]. Paroxysmal AF attacks emerged in 53% of our cases.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Atrial fibrillation is observed in 7 to 40% of the cases after coronary bypass surgery [30,31]. Paroxysmal AF attacks emerged in 53% of our cases.…”
Section: Discussionmentioning
confidence: 85%
“…If the duration of cross-clamping is longer than 90 minutes, the need for inotropics increases [31]. In 23 (76%) of our cases, a need for an inotropic (7-15 microgram/kg/min dopamine) developed.…”
Section: Discussionmentioning
confidence: 94%
“…Compared with consultants, trainees' cases experienced longer aortic cross-clamp times even after propensity-score matching, reflecting the inherent learning curve associated with surgery in general, and perhaps mitral surgery in particular. However, these differences have not been shown to necessarily increase mortality rates [11][12][13]. Indeed, no difference in 30-day mortality was observed amongst the matched pairs.…”
Section: Discussionmentioning
confidence: 88%
“…We believe that inclusion bias might explain this, as patients with the greatest impairment of LV function are unlikely to undergo surgery due to the prohibitive mortality. Secondly, improvements in myocardial protection with the use of retrograde room temperature cardioplegia 14,15 have been shown to reduce early morbidity. This coupled with advances in medical care of patients with LV dysfunction, such as the routine use of ACE inhibitors 16 and more recently beta blockade 17 would be expected to alter the natural history of the disease, improving survival.…”
Section: Discussionmentioning
confidence: 99%